In The Arena : A Memoir of Victory, Defeat, and Renewal - Nixon, Richard (Rawalpindi, Pakistan Services Book Club, 1992)
The former president shares his private thoughts and feelings on his political career, other leaders, and the state of the world.
Include Index
Keywords: Presidents -- United States -- Politics and Government